O ensino de física em Moçambique: um estudo do currículo prescrito da 8ª Classe do Ensino Secundário Geral - Cabrera, Migdalia Rodríguez (2012)
This research aimed to describe, characterize and analyze the prescribed curriculum of 8th Grade of discipline of physics in Secondary School in Mozambique and its relations with the curriculum expressed in the documents of previous years. It s delimited the following hypothesis: the official policy proposals which governing the current Mozambican educational system arise from global reform movement governed by international organisms. As methodological procedure was carried a documental research in which it s important to highlight the existence and access to official proposals which normalize and guide the discipline of physics in secondary school and the curriculum programs of the discipline of physics in the 8th Grade (2004, 2006 and 2008) in Mozambique belonging to the political actions and components of the thematic field of Science Teaching. In the documental analysis were included the official proposals which regulate the teaching process of discipline of physics in the 8th Grade of General Secondary School in the Mozambican educational system: Five-year Program of Government (2005 2009), Strategic Plans of Education and Culture (1999 2003) and (2006 2010/2011), the Curricular Plan of the General Secondary School (2007) and the Curricular Programs of Physics the 8th Grade (2004, 2006 and 2008) of the General Secondary School. In the data analysis, we seek to select and classify the principles and standards of action adopted, based on the contributions of Chervel (1990), Goodson (1997) and Gimeno Sacristán (1998 and 2000). The introduction of new Curricular Programs in the 8th Grade of General Secondary School didn t result positive changes for the teaching of physics at the prospect of delivering broader and deeper education. Otherwise, cause movements in the area four proposals in five years. The few changes have made teaching more pragmatic, impoverished and prepared for market